Amyotrophic Lateral Sclerosis and Myasthenia Gravis Overlap Syndrome: A Review of Two Cases and the Associated Literature - Tai, Hongfei; Cui, Liying; Guan, Yuzhou; Liu, Mingsheng; Li, Xiaoguang; Huang, Yan; Yuan, Jing; Shen, Dongchao; Li, Dawei; Zhai, Feifei (Frontiers in Neurology, 2017)
Objective: To describe the characteristics of patients with amyotrophic lateral sclerosis (ALS) and myasthenia gravis (MG) overlap syndrome and explore the relationship between the two diseases. Methods: We conducted a search of medical records at Peking Union Medical University Hospital from 1983 to 2015 for coexistence of ALS and MG and searched the PubMed database for all literature describing ALS and MG overlap syndrome published through December 2016. We analyzed the clinical and neurophysiological characteristics of patients by groups according to strict diagnostic criteria. Results：We presented 2 patients in our database with combined ALS and MG, and together with 25 cases reported in the literature, the patients were divided into four groups: 12 patients with MG followed by ALS, 8 patients with ALS followed by MG, 5 ALS patients with false-positive anti-acetylcholine receptor and the other 2 ALS patients with only myasthenia symptoms. Most patients had limb-onset ALS, and myasthenia symptoms mainly affected ocular and bulbar muscles. Clinical and neurophysiological characteristics were summarized. Conclusions: These findings support the conclusion that immunological mechanisms and alterations in the neuromuscular junction are related to ALS pathogenesis.